2021
DOI: 10.1002/jee.20428
|View full text |Cite
|
Sign up to set email alerts
|

Why Australian female high school students do not choose construction as a career: A qualitative investigation into value beliefs about the construction industry

Abstract: Background: The construction industry remains male dominated, despite the efforts of business and educational institutions to attract women into construction careers. Previous research has examined why female university students study construction management or engineering. To complement this knowledge, there is an opportunity to understand why so many Australian female high school students do not choose to pursue construction-related careers.Purpose: Framed in motivational theory, the purpose of the study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Many believed that the political impacts and the One Belt One Road initiative had become the means to encourage women in engineering, particularly Thai women in engineering, into the international arena. Also, the participants further argued that their lectures and images would influence the social stigma and challenges for women in engineering and engineering students in developing countries and regions (Dennehy and Dasgupta, 2017;McCullough, 2019;Carnemolla and Galea, 2021). This finding also echoed previous research (Ballen et al, 2017), which suggests that modelling from others may influence individuals' and groups' motivations and career decisions.…”
Section: Surrounding Environments and Individuals: The One Belt One R...supporting
confidence: 69%
See 1 more Smart Citation
“…Many believed that the political impacts and the One Belt One Road initiative had become the means to encourage women in engineering, particularly Thai women in engineering, into the international arena. Also, the participants further argued that their lectures and images would influence the social stigma and challenges for women in engineering and engineering students in developing countries and regions (Dennehy and Dasgupta, 2017;McCullough, 2019;Carnemolla and Galea, 2021). This finding also echoed previous research (Ballen et al, 2017), which suggests that modelling from others may influence individuals' and groups' motivations and career decisions.…”
Section: Surrounding Environments and Individuals: The One Belt One R...supporting
confidence: 69%
“…Although they are well-prepared, women in engineering and STEM workers usually take the frontline and mid-level positions. Another recent study (Carnemolla and Galea, 2021) also argued that lack of awareness and self-alignment, gender gaps, esteem, and influences from other people played significant roles in the career decisions and decision-making processes of women in high school students in engineering. A study (Balakrishnan and Low, 2016) also indicated that the sociocultural factors and views of the general public members also influenced and impacted the decision-making processes of women and groups in the engineering field, particularly women and students who have an interest in engineering.…”
Section: Challenges Of Women Engineering Students: the Situations In ...mentioning
confidence: 99%
“…265 ISSN 1927-2677E-ISSN 1927-2685 have significant impacts on their self-efficacy and sense-making processes (Carnemolla & Galea, 2021;Swart, 2018).…”
Section: Published By Sciedu Pressmentioning
confidence: 99%
“…In fact, some studies with an SCCT perspective have focused on mentoring programs for engineering in higher education (Mendez et al, 2017). Most studies have addressed this topic using other theoretical frameworks (Banerjee et al, 2018; Dos Santos, 2019; Wilkins‐Yel et al, 2019), have not centered on women as a key aim (Fouad et al, 2011; Madamanchi et al, 2019), or have focused on high school students (Carnemolla & Galea, 2021).…”
Section: Social Cognitive Career Theorymentioning
confidence: 99%